Cultural frameworks in Al-Jahez's Renunciation Cultural critical approach - Nasra, Arwa (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research approaches the book of Renunciation from cultural criticism point of view, so the research seeks to capture the cultural frameworks on which the book was based after possible archeological digging of the book's texts to uncover the covered and hidden cultural frameworks assisted by cultural criticism tools to reach this objective and tracing the systematic signs in order to collect them and link them with their associations and then to recreate a concise and brief picture of the bigger text of the ideology from which the texts derive their conceptions and values wether that was by methodological monitoring and conscious or the whole thing was the creation of the subconscious in which the framework was rooted. And because the cultural framework is ramified and rooted, the research preferred to choose models of cultural frameworks present in the book and then divided it to two types; the first has a historical cultural quality and the other has a religious quality in an attempt to clarify the framework's mechanism in imposing its systematic orientation and products.